Ensuring balance reliability in managing the development of electric power systems: condition, problems, information content - Chukreyev Iurii; Chukreyev Mikhail (E3S Web of Conferences, 2023)
The stages of improving the methodological and model support problem of balance reliability in recent years from the standpoint of developing new methodological instructions (MI) on the design of power systems are considered. The analysis of the developed and approved by the Russian Ministry of Energy and the impact of their application on the decisions made.